A Survey: Big data Analysis in Healthcare using machine Learning Approach - Reddy, A. Thammi; Nagendra, M (International Journal of Computer Sciences and Engineering, 2019)
Big Data revolution is transforming the way we live.Healthcare industry generates huge data about every patient but accessing, managing and interpreting the data are critical to creating actionable insights for better care and efficiency.Clinical trends also play a role in the rise of Big Data in Healthcare.Furthermore, big data and machine learning will continually and drastically improve every area of the healthcare industry over the next decade as big data techniques become more refined. This paper presents the role of Big Data analysis in healthcare and various shortcomings of traditional machine learning algorithms.